Lembaga Kekhalifahan sebagai Suatu Institusi Politik - Fitrianto, Achmad Room (el Harakah: Jurnal Budaya Islam, 2010)
The issue of leadership succession has always been an interesting issue of all time. Beside the emergence of the issue of succession and power struggles, the problems of empowering the people and sustaining the civilization are also one of the keys of power transitions. One of the most widely known leadership succession in history is the successions that happened after the death of the Prophet Muhammad saw. This episode  was responded variously by many parties of that time. However, Abu Bakar came up with an awareness that the death of the Prophet Muhammad saw was not the end of anything. There is a huge responsibility to continue the islamic civilization that has been built by the Prophet Muhammad saw. Therefore, the caliphate system was developed and established. At the time of Umar as, the caliphate system was enhanced with the establishment of the Shura Council. Dynamic development of the caliphate system has become an interesting study recently. The system was built based on the divine prophetic system. It was then adopted into a system that puts its main concerns for the society. After some time, the system was degraded by the worldly interests of the Umayyad family who turned it into a monarchy system. However, the development of this system through periods can be analyze in order to gain some valuable lessons for the modern leaderships. Isu suksesi kepemimpinan selalu menjadi isu menarik sepanjang masa. Selain munculnya isu suksesi dan perebutan kekuasaan, masalah pemberdayaan masyarakat dan penengah peradaban juga merupakan salah satu kunci transisi kekuasaan. Salah satu suksesi kepemimpinan yang paling banyak dikenal dalam sejarah adalah suksesi yang terjadi setelah kematian Nabi Muhammad saw. Ini banyak ditanggapi oleh banyak pihak. Namun, Abu Bakar muncul dengan kesadaran bahwa kematian Nabi Muhammad saw saw bukanlah akhir dari apapun. Ada tanggung jawab besar untuk melanjutkan peradaban islami yang telah dibangun oleh Nabi Muhammad saw. Oleh karena itu, sistem khilafah dikembangkan dan didirikan. Pada saat Umar, sistem khilafah ditingkatkan dengan pembentukan Dewan Syura. Perkembangan dinamis sistem khilafah telah menjadi studi menarik baru-baru ini. Sistem ini dibangun berdasarkan sistem nubuatan ilahi. Kemudian diadopsi ke dalam sistem yang menempatkan perhatian utamanya bagi masyarakat. Setelah beberapa lama, sistem itu terdegradasi oleh kepentingan duniawi keluarga Umayyah yang mengubahnya menjadi sistem monarki. Namun, pengembangan sistem ini melalui periode dapat dianalisis untuk mendapatkan beberapa pelajaran berharga bagi kepemimpinan modern.